Strategies to improve clinical research in surgery through international collaboration - Søreide, Kjetil; Alderson, Derek; Bergenfelz, Anders; Beynon, John; Connor, Saxon; Deckelbaum, Dan L; Dejong, Cornelis H; Earnshaw, Jonathan J; Kyamanywa, Patrick; Perez, Rodrigo O, International Research Collaboration in Surgery (IRIS) ad-hoc wo; Othman, Ahmad Faidzal (Elsevier, 2013)
More than 235 million patients undergo surgery every year worldwide, but less than 1% are enrolled in surgical clinical trials—few of which are international collaborations. Several levels of action are needed to improve this situation. International research collaborations in surgery between developed and developing countries could encourage capacity building and quality improvement, and mutually enhance care for patients with surgical disorders. Low-income and middle-income countries increasingly report much the same range of surgical diseases as do high-income countries (eg, cancer, cardiovascular disease, and the surgical sequelae of metabolic syndrome); collaboration is therefore of mutual interest. Large multinational trials that cross cultures and levels of socioeconomic development might have faster results and wider applicability than do single-country trials. Surgeons educated in research methods, and aided by research networks and trial centres, are needed to foster these international collaborations. Barriers to collaboration could be overcome by adoption of global strategies for regulation, health insurance, ethical approval, and indemnity coverage for doctors.